Letter from M. Bolton to James Curtis Booth, June 27, 1854 - Bolton, Mary (1854)
Family news relayed to James Curtis Booth (1810-1888) from his aunt, Mary Bolton.
Keywords: Booth, James Curtis, 1810-1888